1996
DOI: 10.1136/gut.39.6.800
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Helicobacter pylori cytotoxin derived from two areas of Japan with different prevalence of atrophic gastritis.

Abstract: Background andAim-To clarify the roles of Helicobacter pylorn cytotoxin in gastric atrophy, the cytotoxin positive rate and cytotoxin activity in Fukui and Okinawa, where the prevalence of atrophic gastritis and gastric cancer risk are quite different, were studied. Materials-Seventy three strains from Fukui and 51 from Okinawa were examined. Methods-The validation of atrQphy was done by endoscopy, being confirmed with histology. The supernatant of liquid H pylori culture media was concentrated 20-fold, serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…However, two dispase, vacuolating cytotoxin, and cytotoxin-associated antigen (CagA). [27][28][29][30][31][32] Blaser et al reported that infection tinct potential mechanisms can be proposed. First, the HLA-DQA1 gene itself may be one of the genes responwith a cagA positive H. pylori strain in comparison with a cagA negative strain increases the risk of the sible for the association.…”
Section: Discussionmentioning
confidence: 99%
“…However, two dispase, vacuolating cytotoxin, and cytotoxin-associated antigen (CagA). [27][28][29][30][31][32] Blaser et al reported that infection tinct potential mechanisms can be proposed. First, the HLA-DQA1 gene itself may be one of the genes responwith a cagA positive H. pylori strain in comparison with a cagA negative strain increases the risk of the sible for the association.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of H. pylori in Okinawa is not significantly different from other parts of Japan (17,25), the incidence of gastric cancer (6.3 deaths/100,000 population) in Okinawa is the lowest in Japan (mean mortality rate of Japan, 11.8 deaths/100,000 population in 2009) ( . The different environmental factors and diets in Okinawa compared to mainland Japan are thought to be one reason for the lower incidence of gastric cancer (43).…”
mentioning
confidence: 99%
“…Atrophic gastritis is a quite common consequence of H. pylori gastritis in South Korea and Japan. 23 It will develop on a multifactorial basis including dietary factors and aging. 24 Autoimmune mechanisms are very rare in 25 When H. pylori infection spreads to oxyntic mucosa, it induces atrophy of the gastric corpus, which results in reduced secretion of gastric acid.…”
Section: Discussionmentioning
confidence: 99%